Developing a Passive Energy Consumption Reduction Solution - Cherkaoui Marwane; Mouhat Ouadia; Rougui Mohamed; Oukmi Hasna (E3S Web of Conferences)
This study focuses on optimizing the energy efficiency of polyethylene tunnel greenhouses in Mediterranean climates using Design Builder and EnergyPlus software. The research examines the impact of different greenhouse orientations and opening configurations on energy consumption for heating and cooling. The east-west (90°) orientation was found to be the most effective in reducing cooling needs during summer while slightly increasing winter heating requirements. Various opening configurations were tested, including 0%, 20%, 40%, 60%, 80%, and 100%, with openings positioned at the bottom on one side and the top on the opposite side. The 20% opening configuration was identified as optimal for annual energy management. However, a monthly adaptive planning strategy was developed to further enhance energy efficiency. This planning involves keeping the greenhouse closed during winter, using 100% openings in summer, and 20% openings during transitional months. The proposed monthly planning resulted in a significant reduction in energy consumption, decreasing daytime usage by 27.3%, night time usage by 29%, and overall annual energy consumption by 27.6%. This research demonstrates that strategic orientation and adaptive opening management can substantially improve the energy efficiency of greenhouses in Mediterranean climates.